Household Financial Management Among the Community Within the Nyori or Passolo Tradition in Jeneponto Regency - Nabila Nabila; Wa Ode Rayyani (Penerbit Goodwood, 2026)
Purpose: This study analyzes how households in Jeneponto Regency manage their finances while meeting the demands of the Nyori or Passolo tradition, and identifies the effect of this tradition on family economic conditions.Methodology: A descriptive qualitative approach grounded in phenomenology was used, focusing on households in Jeneponto Regency that actively practice the Nyori or Passolo tradition. Data were gathered through in-depth interviews and observation, then analyzed following the Miles, Huberman, and Saldana model, with source and technique triangulation to check consistency. Results: Households in Jeneponto Regency apply several financial strategies, including setting money aside specifically for the tradition, curbing consumptive spending, and drawing on supplementary income such as harvest proceeds to meet Nyori or Passolo obligations. The tradition carries clear economic consequences while also reinforcing social solidarity and kinship ties.Conclusions: A household's success in sustaining the Nyori or Passolo tradition depends heavily on its financial planning capacity, which allows economic needs and social obligations to be balanced.Limitations: The study is confined to households in Jeneponto Regency with a limited number of informants, so the findings cannot yet be generalized to all communities with similar traditions.Contribution: The study enriches scholarship on household financial management within a local cultural context and offers a reference point for government and community efforts to strengthen family financial literacy.